Effects of Acute Handling Stress on Expression of Growth‐Related Genes in Pampus argenteus. Issue 1 (4th July 2016) - Sun, Peng; Yin, Fei; Tang, Baojun
Abstract: In fish, growth and development are mainly regulated by growth hormone/insulin‐like growth factors. Common aquaculture practices subject fish to stress. To investigate the effects of acute stress on growth‐related genes in cultured fish, the expression of growth hormone receptors ( ghr 1 and ghr 2), insulin‐like growth factor binding proteins ( igfbp 1, igfbp 4, and igfbp 5), preprosomatostatin I and II ( ppss 1and ppss 2), somatostatin receptors ( sstr 2 and sstr 5), myostatin ( mstn 1 and mstn 2), and glucocorticoid receptors ( gr 1 and gr 2) were examined in Pampus argenteus subjected to handling stress. Plasma growth hormone levels increased significantly and peaked at 12 h and then decreased significantly at 24 h after treatment ( P <0.05). Plasma cortisol and glucose concentrations in stressed fish began to increase significantly at 2 and 6 h after treatment, respectively. Real‐time quantitative polymerase chain reaction analysis showed that hepatic ghr 2 mRNA levels in liver and muscle decreased sharply in response to the stressor. Igfbp 1, 4, and 5 mRNA expressions in muscle also decreased sharply after exposure, while expression of ppss 1, sstr 2, and mstn 2 increased significantly. This study showed that acute handling stress can affect expression of growth‐related genes in P. argenteus . Our findings could be helpful for the further study on response to stress in this species.